Persepsi Rangkap Jabatan Kepala Sekolah di SMPN Slahung - Setia Ningrum; Sulton Hidayah; Teo Rahmat Josh One; Yuliana Ulinasika; Yuyun Badriyah Wahyumi; Nurul Malikah (Tamilis Synex: Multidimensional Collaboration, 2024)
Dual position is a condition in which a person holds more than one position or position at the same time. The incident of dual office of school principal is an interesting issue to pay attention to, because school principals have a strategic role in managing and advancing the quality of education in the school they lead. This study aims to analyze the factors that cause dual positions, the challenges faced, the impacts caused, and the strategies carried out on the dual position event. The method used in this study is qualitative through interviews with resource persons, namely the principal of SMPN SLAHUNG. The results of the study show that the dual position of principal at SMPN SLAHUNG occurs because there is a vacancy in the position of the principal and the education office appoints the principal who has become the Acting Principal (PLT). The challenges faced are double workload, lack of attention from teachers in carrying out their duties, mental and physical fatigue. The impact is supervision that cannot be direct, time management in dividing tasks must be good, and meetings that cannot be face-to-face in one school. The strategy carried out is good time management, management with related staff in carrying out the duties of the principal who is concurrent, there is a control function in carrying out the duties of the principal and maintaining commitment.